Menjadi Moderat dengan Pendekatan Living Values Education bagi Mahasantri - Arbi, Arbi; Herlina, Herlina; Sofiandi, Sofiandi; Hanafi, Imam; Hasanah, Nur (MENARA RIAU, 2024)
Currently, the Muslim community in Indonesia is experiencing a 'conservative turn.' Several radical group movements seem to be expanding their roles in various dimensions of community life, including education. Many surveys corroborate this condition. The symptoms of intolerance have also entered the activities at Ma’had Al-Jamiah UIN Suska Riau, an "elite" institution that provides a space for learning about religious values. Through the Living Values Education (LVE) approach, teachers are trained in the values of religious moderation for students of Ma’had Al-Jamiah UIN Suska Riau. This research uses the Participatory Action Research (PAR) approach. Twenty students were randomly selected and provided with understanding through the Living Values Education (LVE) approach. The research results indicated an increase in students' understanding of moderate religion after being educated in living values. These findings are useful for policymakers to implement this study model in promoting religious moderation among the Muslim community.